Influence of Nisin-Biogel at Subinhibitory Concentrations on Virulence Expression in Staphylococcus aureus Isolates from Diabetic Foot Infections - Carolina Jesus; Rui Soares; Eva Cunha; Miguel Grilo; Luís Tavares; Manuela Oliveira (MDPI AG, 2021)
A new approach to diabetic foot infections (DFIs) has been investigated, using a nisin-biogel combining the antimicrobial peptide (AMP) nisin with the natural polysaccharide guar-gum. Since in in vivo conditions bacteria may be exposed to decreased antimicrobial concentrations, known as subinhibitory concentrations (sub-MICs), effects of nisin-biogel sub-MIC values corresponding to 1/2, 1/4 and 1/8 of nisin's minimum inhibitory concentration (MIC) on virulence expression by six Staphylococcus aureus DFI isolates was evaluated by determining bacteria growth rate; expression of genes encoding for staphylococcal protein A (spA), coagulase (coa), clumping factor A (clfA), autolysin (atl), intracellular adhesin A (icaA), intracellular adhesin D (icaD), and the accessory gene regulator I (agrI); biofilm formation; Coa production; and SpA release. Nisin-biogel sub-MICs decreased bacterial growth in a strain- and dose-dependent manner, decreased agrI, atl and clfA expression, and increased spA, coa, icaA and icaD expression. Biofilm formation increased in the presence of nisin-biogel at 1/4 and 1/8 MIC, whereas 1/2 MIC had no effect. Finally, nisin-biogel at sub-MICs did not affect coagulase production, but decreased SpA production in a dose-dependent manner. Results highlight the importance of optimizing nisin-biogel doses before proceeding to in vivo trials, to reduce the risk of virulence factor's up-regulation due to the presence of inappropriate antimicrobial concentrations.